AKTOR DAN RELASI KEKUASAAN DALAM PENGELOLAAN MANGROVE DI KABUPATEN PESAWARAN, PROVINSI LAMPUNG, INDONESIA - Indra Gumay Febriano; Didik Suhardjito; Dudung Darusman; Cecep Kusmana; Aceng Hidayat (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2015)
Politicization of environment has led to environmental degradation and community marginalization. The purpose of this research is to elucidate and verify actors and power relation occurred in mangrove management. Research results show that policies of regency government did not run well nor effective, as businessmen are able to converse mangrove into intensive shrimp ponds. NGO and community are making joint efforts to prevent further conversion of remaining mangrove but they are not strong enough to face the access of businessmen. Accordingly, it is necessary to develop larger network through collaboration in order to drive regency government policies to support mangrove management in a more sustainable way. Another way to carry out is by building relation with businessmen through academicians as parts of the above networking to educate businessmen about the importance of mangrove functions and advantages in order to achieve not only environmental sustainability but also shrimp aquaculture and people‟s livelihood sustainability. The success of local community organization greatly assisted the regency government in the development of rural community in its coastal areas. Mangrove conservation can be synergized by creating opportunities in improving people's livelihood alternatives and ultimately will reduce the pressure on mangroves.